Collaborating, Connecting, and Clustering in the Humanities: A Case Study of Networked Scholarship in an Interdisciplinary, Dispersed Team. (May 2015) - Quan-Haase, Anabel; Suarez, Juan Luis; Brown, David M.
To what extent does networked scholarship in the humanities parallel established models in the sciences? The present study examines the connections of a 7-year interdisciplinary, dispersed, collaborative network composed of 33 humanities scholars investigating the Hispanic Baroque. Our findings suggest that project membership leads to greater network density and integration, without necessarily increasing the level of in-depth collaboration typically found in the sciences. Hence, collaborative models in the humanities, while increasingly important, are distinct from their counterparts in the sciences. The study provides a more nuanced view of networked scholarship because it demonstrates that large-scale collaborative projects can yield a high level of integration of the overall network, while at the same time allowing for strong thematic clustering. This dual structural process is relevant because not all network members can form dense relations with one another. Furthermore, we identified that principal investigators showed different networking strategies.